Kinetics of calcium phosphate nucleation and growth on calcite: Implications for predicting the fate of dissolved phosphate species in alkaline soils - Wang, L.; Ruiz-Agudo, E.; Putnis, Christine; Menneken, M.; Putnis, Andrew (2012)
Unraveling the kinetics of calcium orthophosphate (Ca-P) precipitation and dissolution is important for our understanding of the transformation and mobility of dissolved phosphate species in soils. Here we use an in situ atomic force microscopy (AFM) coupled with a fluid reaction cell to study the interaction of phosphate-bearing solutions with calcite surfaces. We observe that the mineral surface-induced formation of Ca-P phases is initiated with the aggregation of clusters leading to the nucleation and subsequent growth of Ca-P phases on calcite, at various pH values and ionic strengths relevant to soil solution conditions. A significant decrease in the dissolved phosphate concentration occurs due to the promoted nucleation of Ca-P phases on calcite surfaces at elevated phosphate concentrations and more significantly at high salt concentrations. Also, kinetic data analyses show that low concentrations of citrate caused an increase in the nucleation rate of Ca-P phases. However, at higher concentrations of citrate, nucleation acceleration was reversed with much longer induction times to form Ca-P nuclei. These results demonstrate that the nucleation-modifying properties of small organic molecules may be scaled up to analyze Ca-P dissolution-precipitation processes that are mediated by a more complex soil environment. This in situ observation, albeit preliminary, may contribute to an improved understanding of the fate of dissolved phosphate species in diverse soil systems. © 2011 American Chemical Society.